Good Living: (de)Colonial Perspective from Indigenous Communities (Revista Rupturas, 2017)
In this article, it is proposed to explore the semantic field of the theme "Good Living" as opposed to the civilizational and environmental crisis based by capitalism and its individualism and rationalism ideological. The study employed a descriptive and qualitative methodology with comparative analysis through semi-structured interviews with ten university students from indigenous communities Warequena, Baníwa, Xukuru do Orurobá, Tariána, Terena (Bananal and Cachoeirinha), Arapaso and Atikum-Umã. The results demonstrate that Good Living is a resistance processes of indigenous communities, face the environmental, cultural and economic conflicts resulting of the dominant productivist thinking.
Keywords: Good Living; indigenous communities; colonization; interculturalism